Transcriptomic immune profiles of human flavivirus‐specific T‐cell responses. Issue 1 (7th January 2020) - Grifoni, Alba; Tian, Yuan; Sette, Alessandro; Weiskopf, Daniela
Summary: The Flavivirus genus of viruses includes dengue (DENV), Zika (ZIKV), yellow fever (YFV), Japanese encephalitis (JEV), and West Nile (WNV) viruses. Infections with these species combined are prevalent in tropical and sub‐tropical areas, affecting millions of people and ranging from asymptomatic to severe forms of the disease. They therefore pose a serious threat to global public health. Several studies imply a role for T cells in the protection but also pathogenesis against the different flavivirus species. Identifying flavivirus‐specific T‐cell immune profiles and determining how pre‐exposure of one species might affect the immune response against subsequent infections from other species is important to further define the role of T cells in the immune response against infection. Understanding the immune profiles of the flavivirus‐specific T‐cell response in natural infection is important to understand the T‐cell response in the context of vaccination. In this review, we summarize the current knowledge on human immune profiles of flavivirus‐specific T‐cell reactivity, comparing natural infection with the acute form of the disease and vaccination in different flavivirus infections. Abstract : Understanding the complexity of T‐cell responses is important in flaviviruses and requires investigation in different contexts, from natural infection to vaccination. Transcriptomic studies help with the in‐depth characterization of T‐cell responses, identifying protective immune profiles against severe disease forms or common profiles across flavivirus species. Following this concept, in this review, we summarize transcriptomic studies focused on dissecting flavivirus T‐cell‐specific immune profiles and identify common profiles across several flaviviruses and current gaps of knowledge.